Analisis Korelasi Kemampuan Literasi Sains dengan Hasil Belajar Materi Gas Ideal Pada Mahasiswa Pendidikan Fisika - Alifia Aminingrum; Sudarti , Sudarti; Subiki , Subiki (Program Studi Pendidikan Fisika FKIP Universitas PGRI Palembang, 2025)
In the 21st century, various sectors continue to experience development, one of which is the education sector. Education aims to create a generation that is superior and able to compete in the face of global competition. The ability to apply science concepts to find solutions to scientific problems or phenomena based on scientific evidence is called scientific literacy. Literacy skills are not limited to reading and writing skills, but involve thinking skills. The purpose of this study was to determine the relationship between students' science literacy skills and the learning outcomes of Physics Education students on Ideal Gas material. The research method used is a quantitative method that aims to test the theory. Data processing was carried out using IBM SPSS version 23. From the experiment, it can be seen that there is a relationship between science literacy skills and physics learning outcomes of students on ideal gas material. Both variables correlate strongly. So that when one variable increases in value, the value of the other variable will also increase and vice versa.